2019
DOI: 10.1093/abbs/gmz099
|View full text |Cite
|
Sign up to set email alerts
|

TIPE1 suppresses the invasion and migration of breast cancer cells and inhibits epithelial-to-mesenchymal transition primarily via the ERK signaling pathway

Abstract: Tumor necrosis factor α-induced protein 8-like-1 (TIPE1) functions as an activator or a repressor in a tumor cell type-specific manner. However, the role of TIPE1 in breast cancer, especially regarding metastasis, is unknown. In this study, we aimed to investigate the TIPE1 expression in breast cancer tissues, the biological functions, and the underlying mechanisms of TIPE1 regarding the metastatic properties of breast cancer cells. The results of immunohistochemical staining and western blot analysis indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
2
12
1
Order By: Relevance
“…Activation of NFkB by TNFα promotes breast cancer by promoting (Kawabata et al, 2017). TNFα signaling also activates the ERK/JNK/p38 pathway leading to migration and invasion in colon cancer cells (Zhao and Zhang, 2018), and breast cancer cells (Qiu et al, 2019). Another study demonstrated that TNFα activates mesenchymal stromal cells that leads to metastasis in breast cancer through the recruitment of CXCR2+ neutrophils (Yu et al, 2017).…”
Section: Analysis Of Genetic Alterations Of the Pbmentioning
confidence: 99%
“…Activation of NFkB by TNFα promotes breast cancer by promoting (Kawabata et al, 2017). TNFα signaling also activates the ERK/JNK/p38 pathway leading to migration and invasion in colon cancer cells (Zhao and Zhang, 2018), and breast cancer cells (Qiu et al, 2019). Another study demonstrated that TNFα activates mesenchymal stromal cells that leads to metastasis in breast cancer through the recruitment of CXCR2+ neutrophils (Yu et al, 2017).…”
Section: Analysis Of Genetic Alterations Of the Pbmentioning
confidence: 99%
“…22 TIPE1 is also present in many cancer cells of epithelial origin, including breast, cervical, bladder and gastric cancer cells. 11,13,[22][23][24][25] To date, a great deal of evidence has shown that TIPE1 plays crucial roles in the carcinogenesis of many cancers, including hepatocellular carcinoma, gastric cancer, lung cancer, osteosarcoma, cervical Autophagy has been shown to be intimately related with cancer. [27][28][29] In this study, the decreased density of characteristic autophagosomes and the decreased expression of LC3B in tumour tissue sections provided strong evidence that autophagy was inhibited after TIPE1 was overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…22 TIPE1 is also present in many cancer cells of epithelial origin, including breast, cervical, bladder and gastric cancer cells. 11,13,[22][23][24][25] To date, a great deal of evidence has shown that TIPE1 plays crucial roles in the carcinogenesis of many cancers, including hepatocellular carcinoma, gastric cancer, lung cancer, osteosarcoma, cervical cancer, colon cancer and breast cancer. TIPE1 can induce apoptosis in RAW264.7 and hepatocellular carcinoma cells by increasing the levels of Bcl-2 family proteins or down-regulating the Rac1 pathway.…”
Section: Tipe1 Promotes Tumour Growth By Inhibiting Autophagy Via Tmentioning
confidence: 99%
“…23 Additionally, in breast cancer cells, TIPE1 suppressed the proliferation, invasion, metastasis, and EMT via downregulating the phosphorylation of extracellular signal-regulated protein kinase (ERK). 24 In osteosarcoma, TIPE1 was found to suppress the activity of monocyte chemotactic protein-1 (MCP-1) to reduce macrophage infiltration, thus inhibiting the proliferation of osteosarcoma cells [38]. 25 In hematological diseases, TIPE1 was observed to promote cell apoptosis and inhibit tumor growth in RAW264.7 cells by upregulating pro-apoptotic members of the B cell lymphoma/leukemia-2 (Bcl-2) family.…”
Section: Tipe1mentioning
confidence: 99%